Silicon Waveguide Integrated with Germanium Photodetector for a Photonic-Integrated FBG Interrogator - Hongqiang Li; Sai Zhang; Zhen Zhang; Shasha Zuo; Shanshan Zhang; Yaqiang Sun; Ding Zhao; Zanyun Zhang (Nanomaterials, 2020)
We report a vertically coupled germanium (Ge) waveguide detector integrated on silicon-on-insulator waveguides and an optimized device structure through the analysis of the optical field distribution and absorption efficiency of the device. The photodetector we designed is manufactured by IMEC, and the tests show that the device has good performance. This study theoretically and experimentally explains the structure of Ge PIN and the effect of the photodetector (PD) waveguide parameters on the performance of the device. Simulation and optimization of waveguide detectors with different structures are carried out. The device’s structure, quantum efficiency, spectral response, response current, changes with incident light strength, and dark current of PIN-type Ge waveguide detector are calculated. The test results show that approximately 90% of the light is absorbed by a Ge waveguide with 20 μm Ge length and 500 nm Ge thickness. The quantum efficiency of the PD can reach 90.63%. Under the reverse bias of 1 V, 2 V and 3 V, the detector’s average responsiveness in C-band reached 1.02 A/W, 1.09 A/W and 1.16 A/W and the response time is 200 ns. The dark current is only 3.7 nA at the reverse bias voltage of −1 V. The proposed silicon-based Ge PIN PD is beneficial to the integration of the detector array for photonic integrated arrayed waveguide grating (AWG)-based fiber Bragg grating (FBG) interrogators.